A comparative study on glass and carbon fibre reinforced laminated composites in scaled quasi-static indentation tests. (1st August 2020) - Fotouhi, Mohamad; Damghani, Mahdi; Leong, Mun Choong; Fotouhi, Sakineh; Jalalvand, Meisam; Wisnom, Michael R.
Abstract: This paper investigates the effect of fibre properties of composite structures on the mechanical performance and formation of low-velocity impact damage. Quasi-static indentation tests were conducted on a comprehensive set of scaled Quasi Isotropic (QI) S-glass/8552 epoxy and QI IM7-carbon/8552 epoxy laminates, comparing changes in both in-plane dimensions and fully three-dimensionally scaled cases. Due to the higher thickness of the S-glass laminates, the mechanical results were normalized by a thickness scaling rule to have a fair comparison between the mechanical behaviour. The results demonstrated that the shape of the load-displacement of the S-glass/epoxy laminates is similar to that of the IM7-carbon laminates, with evident changes in rigidity appearing due to the onset and propagation of delamination and final failure caused by fibre breakage. The S-glass/8552 epoxy laminates had smaller load drops, higher deflection and higher mechanical energy absorption before failure compared to the IM7-carbon/8552 epoxy laminates. X-ray computed tomography scanning revealed that delamination is the dominant failure mode for the investigated laminates, and the shape of delamination was influenced by the ply angles at the interfaces. Comparing the glass and carbon laminates, ultrasonic C-scan results indicated similar delamination damage size for the initiation stage, however the damage size was found to be dependent on the fibre properties and layup sequence in the propagation stage.